A Randomized Controlled Trial of Ultrasound Versus Nerve Stimulator Guidance for Axillary Brachial Plexus Block. Issue 6 (November 2016) - Barrington, Michael J.; Gledhill, Samuel R.; Kluger, Roman; Clarke, Alexander L.; Wong, Daniel M.; Davidson, Henry; Thomas, Rowan
Abstract : Background: Ultrasound-guided techniques improve outcomes in regional anesthesia when compared with traditional techniques; however, this assertion has not been studied with novices. The primary objective of this study was to compare sensory and motor block after axillary brachial plexus block when performed by novice trainees allocated to an ultrasound- or nerve–stimulator-guided group. A secondary objective was to compare the rates of skill acquisition between the 2 groups. Methods: This study was a prospective, randomized, observer-blinded, 2-arm controlled trial. Anesthesia trainees participating in this trial were novices to axillary brachial plexus block and sonography. All trainee participants underwent a standardized training program. The primary outcome was combined sensory and motor block in the relevant territories 30 minutes after completion of block. A global rating scale was used to assess trainee block performance. Results: The study was ceased after 12 trainees completed 153 blocks. There was no difference between groups in combined motor/sensory score ( P = 0.28) or as a function of block number ( P = 0.38). There was no difference in onset between groups ( P = 0.38). In both groups, there was an increase in the global rating scale score ( P < 0.0001) and reduced preblock survey and block performance times ( P = 0.001) with experience. Conclusions: We were unable to demonstrate a difference in the efficacy of axillary brachial plexus block performed by novices when ultrasound guidance was compared with a nerve stimulator technique. There was evidence of similarly improved clinical performance of novices in both groups.